Image – Face – Mask in figurative painting by Kazimir Malevich, 1928–1933. On the problem of Russian avant-garde imagery - Furman, Olga V. (Actual Problems of Theory and History of Art, 2012)
Image, face and mask are important notions in the general system of avant-garde painting at the beginning of the 20th century. Th ey found their expression in many works of the Russian avant-garde artists and in the works of Kazimir Malevich as well. In what forms are these notions realized in Malevich’s painting created aft er Suprematism? How do they integrate into the whole ,Suprematist system and what sense do they bear in works of Malevich? These questions are the main subject of this paper.